Endothelin-1 expression in prostate needle biopsy specimens correlated with aggressiveness of prostatic cancer - Mojgan Asgari; Elham Eftekhar; Maryam Abolhasani; Hossein Shahrokh (Iranian Society of Pathology, 2017)
Background & Objective: As the prostate adenocarcinoma is one of the most common malignant tumors in males, looking for a marker to effectively predict aggressiveness and metastatic potential in an apparently localized cancer in initial needle biopsy specimens can help the clinicians to make more appropriate decision for treatment, planning, and choosing appropriate targeted therapy. The present study assessed the value of Endothelin-1 expression to predict prognosis of prostatic cancer Methods: In a cross sectional study, 83 patients who underwent radical prostatectomy in Hasheminejad Kidney Center in 2008 through 2012 were assigned to two groups including 43 with and 40 without extra-prostatic extension (EPE). Endothelin-1 staining was performed on Paraffin Embedded blocks of preoperative needle biopsies. Results: The expression of Endothelin-1 increased in 72% of patients in the group with EPE (P<0.001). The group with Endothelin-1 positivity showed higher serum level of prostate specific antigen (PSA) (p = 0.039). Endothelin-1 expression was positive in 67% of patients with perineurial invasion (P<0.001). Adjusting the baseline variables of PSA and PN in a multivariable logistic regression model, the Endothelin-1 positivity could effectively predict EPE in patients with prostatic cancer (OR: 5.46, p = 0.010). Conclusion: Correlation of Endothelin-1 expression in needle biopsy specimens in expected with extra-prostatic extension of tumor in radical prostatectomy specimens, perineurial invasion and serum PSA level at the time of diagnosis.